1990
DOI: 10.1073/pnas.87.10.3962
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of germ-line immunoglobulin A transcripts produced during transforming growth factor type beta-induced isotype switching.

Abstract: The addition of transforming growth factor type (3 to lipopolysaccharide-stimulated murine B-cell cultures enhances isotype switching to IgA and induces the appearance of two sizes of a mRNA transcripts. One of these is the same size as mRNA for secreted IgA but the other, which is 300-400 base pairs (bp) shorter, does not correlate in size with any form of productive a mRNA. Both sizes of transcript were shown to contain germ-line sequences 5' to the a switch region, suggesting that the longer transcripts inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(53 citation statements)
references
References 32 publications
6
47
0
Order By: Relevance
“…8). IgA class-switching in sIgM ϩ sIgA Ϫ B cells has been shown to precede the synthesis of germline C␣ mRNA transcripts (49). In contrast, it was found that intestinal and splenic sIgM ϩ sIgA Ϫ B-2 cells did not express C␣ transcript-specific mRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…8). IgA class-switching in sIgM ϩ sIgA Ϫ B cells has been shown to precede the synthesis of germline C␣ mRNA transcripts (49). In contrast, it was found that intestinal and splenic sIgM ϩ sIgA Ϫ B-2 cells did not express C␣ transcript-specific mRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In response to stimulation of mature B cells by interleukins and/or other T-cell-or macrophageproduced factors, nuclear proteins (73) would bind to the tandem repeat area of the ,u locus. In response to other interleukins and other factors, the second portion of the switch complex would form near a downstream tandem repeat (switch) region (68), perhaps after the region is made accessible due to germ line (sterile) transcription (32,36,53 (20). The IgH locus inversions and duplications that are attributed to sister chromatid exchange might also be mediated by this mechanism, since switch complexes can assemble on the C of one chromosome and on a CH on another chromosome (16).…”
Section: Discussionmentioning
confidence: 99%
“…This germline transcription likely facilitates the DNA lesion-inducing activity of AID by: 1) promoting chromatin accessibility, 2) AID recruitment via RNA PolII, and 3) generation of a ssDNA target for AID (17)(18)(19). Transcription through the H chain ␣ region is initiated by B cell activation and TGF-␤ signaling (20).…”
Section: Mz B Cells Switch Preferentially To Igamentioning
confidence: 99%